2020
DOI: 10.3390/ai1020015
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Yield Mapping: A Precision Agriculture Approach Based on Machine Learning

Abstract: Carrot yield maps are an essential tool in supporting decision makers in improving their agricultural practices, but they are unconventional and not easy to obtain. The objective was to develop a method to generate a carrot yield map applying a random forest (RF) regression algorithm on a database composed of satellite spectral data and carrot ground-truth yield sampling. Georeferenced carrot yield sampling was carried out and satellite imagery was obtained during crop development. The entire dataset was split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Considering the test dataset, the RF regression had RMSE values ranging from 4.63 to 5.47 Mg ha −1 , which was lower than the MLR model (RMSE closer to 6.0 Mg ha −1 ). Other studies reported RF prediction as more accurate than MLR [2,53].…”
Section: Selection Of Predictor Variablesmentioning
confidence: 97%
“…Considering the test dataset, the RF regression had RMSE values ranging from 4.63 to 5.47 Mg ha −1 , which was lower than the MLR model (RMSE closer to 6.0 Mg ha −1 ). Other studies reported RF prediction as more accurate than MLR [2,53].…”
Section: Selection Of Predictor Variablesmentioning
confidence: 97%
“…On the other hand, Taghizadeh-Mehrjardi et al [51] created a method to assess the suitability of land for two main crops (i.e., wheat and rainfed barley) according to the Organization's "Land Suitability Assessment Framework" for Agriculture and Food (FAO). Wei et al [52] developed a method to generate a carrot yield map applying a random forest regression algorithm on a database composed of satellite spectral data and ground carrot yield sampling. Mosavi et al [53] propose a method that includes new ML models for the susceptibility mapping of soil water erosion.…”
Section: Answer For Rq4: What Is the Area Of Agriculture In Which Big Data Machine Learning Is Used?mentioning
confidence: 99%
“…As observed in other studies, Bayesian networks can investigate appropriate and interpretable framework for the simultaneous modeling of multiple quantitative traits in better predictive power result in the context of additive genetic models [35] Among the other studies that had good performance for example [36] used VW-4DEnSRF algorithm to study the area and winter wheat yield estimation based on the WOFOST crop model and a crop yield assimilation system. Wei, et al [25], study highlighted that despite of the impact machine learning approaches in understanding and exploiting GEI for prediction, there is still some room for expanding and improving their use in applications not yet explored. [37] used the deep learning model such as convolutional neural network (CNN) and artificial neural network (ANN) to Self-Predictable Crop Yield Platform (SCYP) based on crop diseases using deep learning that collects weather information (temperature, humidity, sunshine, precipitation, etc.)…”
Section: Multi Target Performancementioning
confidence: 99%